Exploiting Synergistic Catalysis for an Ambient Temperature Photocycloaddition to Pyrazoles. Issue 1 (29th November 2019) - Lakeland, Christopher P.; Watson, David W.; Harrity, Joseph P. A.
Abstract: Sydnone‐based cycloaddition reactions are a versatile platform for pyrazole synthesis, however they operate under harsh conditions (high temperature and long reaction times). Herein we report a strategy that addresses this limitation utilizing the synergistic combination of organocatalysis and visible‐light photocatalysis. This new approach proceeds under ambient conditions and with excellent levels of regiocontrol. Mechanistic studies suggest that photoactivation of sydnones, rather than enamines, is key to the successful implementation of this process. Abstract : A photo finish ! The synergistic combination of organocatalysis and visible‐light photocatalysis offers a mild route to pyrazoles that proceeds under ambient conditions and with excellent levels of regiocontrol.